Effect of basalt powder and firing temperature on the properties of clay-based composite ma terials (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper presents the results of a study on the development of composite materials based on widely available natural clay from the Nookat deposit, modified with basalt powder from the Kyzyl-Kiya deposit. The aim of the work was to study the influence of the concentration of basalt powder (fraction 10–200 μm, from 0 to 15 wt.%) and firing temperature (900, 950, 1000 °C) on the main physical and mechanical properties of the obtained materials: compressive strength, water absorption and average density. It was found that the introduction of 5% basalt powder and firing at 1000 °C made it possible to obtain a material with maximum compressive strength (up to 18.5 MPa) compared to an unmodified sample. Nonlinear relationships between the additive’s influence on the composite’s properties were identified, driven by changes in the matrix sintering kinetics and the system’s particle size distribution. It was shown that basalt powder acts not as a reinforcing element, but as an active mineral additive influencing the sintering and structure formation processes. The obtained results demonstrate the potential of using natural clay and basalt powder to create effective building composites.
Keywords: composite material, clay, basalt powder, filler, dispersion modification, compressive strength, water absorption, ceramics, firing temperature, fractional composition